Analysis of Stunting Incidents Based on Mother's Knowledge - Marita, Zadam; Okinarum, Giyawati Yulilania; Huda, Mega Hasanul; Dwihestie, Luluk Khusnul (Qualitative and Quantitative Research Center, 2023)
Every parent does not want stunting cases to occur in their children. Stunting in children can be caused by direct and indirect factors. One direct cause is a lack of nutritious food intake. The role of parents, especially mothers, as indirect causes plays a vital role in fulfilling children's nutrition. This research aims to analyze the relationship between a mother's knowledge and the incidence of stunting. The research method uses an analytical survey with a cross-sectional approach. The sampling technique used purposive sampling, totaling 68 respondents, with the criteria being mothers who had toddlers aged 1-2 years. Research location in the city of Bekasi, Indonesia. The research instrument used a questionnaire and measurements of body length compared with age. Data analysis with bivariate and univariate statistics. The research results show that the majority of mothers have good knowledge, and the majority do not experience stunting. Statistical tests using Chi-Square show that there is a significant relationship between mothers' knowledge about nutrition and the incidence of stunting in mothers of toddlers 1-2 years old. The contribution of this research is evidence that mother's knowledge is essential for children's growth. One alternative strategy to overcome the increase in stunting cases is to strengthen the understanding of mothers.